Elucidating the Multi‐Scale Temperature Evolution and Densification Mechanisms of Amorphous Powders During Spark Plasma Sintering: Experiments and Modeling. Issue 5 (17th July 2022) - Ding, Huaping; Bao, Xiaoqian; Zhang, Mao; Tang, Xuefeng; Niu, Yong; Gong, Pan; Wang, Xinyun
Abstract : This work investigates amorphous powders' temperature distribution and densification mechanism at macroscopic and particle scales during spark plasma sintering. The evolution of contact necks between powders is studied by quasi‐in situ microstructure examination. Amorphous powders' contact mode changes from point contact to surface contact as sintering proceeds. The high current density concentration leads to local overheating at the particle necks. As the contact radius ratio increases, the temperature gap between the necks and the interior of the particles becomes less noticeable. In the early stage, localized high temperature and high stress around the necks significantly reduce the densification onset temperature of amorphous powders. As the relative density increases, the uneven temperature field at the particle scale disappears, while the macroscopic temperature gradient increases. The dominant densification mechanism of amorphous powders has transitioned from particle‐scale to macroscopic temperature. The sample temperature is significantly higher than the nominal sintering temperature, promoting the contribution of viscous flow to porosity elimination. This work can provide new insights into the evolution of multi‐scale temperature distribution during spark plasma sintering and its impact on the densification behavior of amorphous powders. Abstract : This work investigates amorphous powders' temperature distribution and densification mechanism at macroscopic and particle scales during spark plasma sintering. Amorphous powders' contact mode changes from point contact to surface contact as sintering proceeds. The highly concentrated current leads to local overheating at the particle necks. The unique multi‐scale densification mechanism promotes the rapid densification of amorphous powders.